Prenatal Diagnosis and Postnatal Management of Meconium Peritonitis - Maidarti, Mila (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To present two cases of fetal meconium peritonitis with perforated ileum and without a definite intestinal obstructive lesion. Case report: Two patients who presented prenatally with ultrasound findings of meconium peritonitis and postnatally were found to have perforation of the terminal ileum and meconium peritonitis. In both cases, the diagnosis of meconium peritonitis was suspected prenatally based on the ultrasound findings which were hyperechogenic bowel and abdominal free fluid with increased echogenicity. Both babies were delivered by c-section due to obstetrical indication. After delivery the babies were admitted to the intensive care unit because of a distended abdomen and respiratory distress. An explorative laparotomy revealed perforations of the ileum, and the pediatric surgeon performed adhesiolysis and ileostomy. The infant recovered well after the operation and was fed uneventfully. Conclusions: Echogenic intraabdominal free fluid was the most common ultrasound findings in meconium peritonitis. Early detection of meconium peritonitis was not indicative of poor neonatal outcomes, and selective termination was not necessary, unless indicated for other reasons. [Indones J Obstet Gynecol 2011; 35-4:191-8] Keywords: prenatal diagnosis, postnatal management, meconium peritonitis